Dictionary for managing trees in urban environments - Draper, Danny B.; Richards, Peter A. (CSIRO Pub. : Institute of Australian Consulting Arborculturists, 2009)
"Dictionary for Managing Trees in Urban Environments is a comprehensive list of terms used in the universal management of urban trees. Many of the terms are from Arboricultural science, while others are derived from unproven but commonly applied concepts. Some new concepts have been introduced where the existing terminology to describe trees was limited or nonexistent. This dictionary allows for broad application and use by a wide variety of people and conveys in plain language concepts that are sometimes complex. Most major terms have been cross referenced and diagrams have been added for greater understanding. Dictionary for Managing Trees in Urban Environments promotes a greater understanding of Arboriculture and Urban Forestry, and will assist in the preparation of reports for the management of trees, procedures and planning instruments, such as Tree Management Policies and Tree Management Orders."--Provided by publisher